Entrepreneurship intentions for students in Jambi Province, Indonesia (Study in response to the implementation of the freedom to learn, independent campus) - Amril Amril; Hardiani Hardiani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study aims to: 1) analyze the characteristics of student entrepreneurial intentions in Jambi Province; 2) Analyze the factors that influence student entrepreneurial intentions in Jambi Province. The main data used are primary data collected from student respondents in Jambi Province. Apart from that, secondary data were also collected related to entrepreneurial aspects from related agencies. Descriptive statistical tools and single or cross-frequency tables were used to analyze respondents' characteristics and entrepreneurial intentions. To analyze the factors that influence student entrepreneurial intentions using the Structural Equation Modeling (SEM) model. The results of the study found that students' interest in entrepreneurship in Jambi Province was relatively high. It shows that there is a high potential for students to become young entrepreneurs in the future. Individual characteristics, attitudinal factors significantly influence this entrepreneurial interest, and contextual factors from students Skills should follow this high interest in entrepreneurship in entrepreneurship. Therefore, in collaboration with central and local governments, universities are advised to develop and improve students' entrepreneurship training.